"...my illness...and necessity drove me to come here..." Don Tomás, a garbage worker - Juan Francisco Cortés Viveros; Ricardo Cuéllar Romero (Social Medicine Publication Group, 2023)
According to Marx, labor power, like all commodities, must be exercised through work. The consumption of the labor power that happens in the immediate production process carries with it diverse consequences in detriment of workers' health. Workers, in general, do not have the possibility to feel and take care of these consequences. In this essay we recover some of the experiences of Don Tomás, a garbage worker who, despite attempts to prevent the diseases he suffers from "sticking" to him, finds it impossible to do the kind of work he wants to do.